The role of innate lymphoid cells in intestinal inflammation - Schaupp, A (2015)
A breakdown of intestinal homeostasis due to dysregulated immune responses against intestinal bacteria underlies the pathogenesis of inflammatory bowel disease (IBD) in genetically susceptible individuals. Amongst mucosal immune cells, innate lymphoid cells (ILCs) are a heterogeneous group of cells whose functions in pathogenic inflammatory processes in the intestine are beginning to emerge from experimental murine models. However, less is known about the role of ILCs in chronic intestinal inflammation in humans. In this thesis, human ILCs were examined in the context of IBD and potential mechanisms by which these cells may contribute to IBD pathogenesis were investigated. We identified phenotypically and functionally distinct ILC1, ILC2 and ILC3 populations in the human intestinal lamina propria and peripheral blood and found that ILCs enriched for expression of IL-17A and IFNγ accumulated in the inflamed intestine, potentially through increased in situ proliferation and chemokine-mediated recruitment from blood. Based on their in situ localization, we investigated potential functional interactions between ILCs and CD4+ T cells and found that a proportion of human ILCs in peripheral blood and the intestinal lamina propria expressed HLA-DR and co-stimulatory molecules. ILCs were capable of taking up and processing protein antigen at levels equivalent to B cells, but in contrast to monocytes, antigen-pulsed ILCs failed to activate antigen-specific memory CD4+ T cells in vitro. Reciprocal activation between ILCs and monocytes enhanced the antigen-presenting potential and bactericidal capacity of myeloid cells and induced upregulation of co-stimulatory ligand expression by ILCs. This innate activation loop resulted in an augmentation of CD4+ T cell activation. These findings extend our knowledge of the complex interactions between human ILCs and other key immune cell populations, and suggest mechanisms by which rare ILCs may contribute to the pathogenesis of IBD by augmenting myeloid cell and CD4+ T cell responses.